2002
DOI: 10.1002/cncr.10329.abs
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of caveolin‐1 in esophageal squamous cell carcinoma correlates with lymph node metastasis and pathologic stage

Abstract: Over-expression of caveolin-1 is associated with lymph node metastasis and a worse prognosis after surgery in esophageal squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…How might the overexpression of Cav-1 and caveolae contribute to the hyperproliferative phenotype of IPAH? Certain neoplasms [i.e., prostate cancer (39,40), bladder cancer (41), adenocarcinomas (42), esophageal squamous cell carcinomas (43), and both benign and malignant smooth muscle tumors (44)] have elevated Cav-1 expression. Timme et al have shown an interplay between Cav-1 and c-Myc-induced apoptosis: the Cav-1 gene can be down-regulated by c-myc, and maintaining high levels of Cav-1 suppresses c-myc-induced apoptosis (45).…”
Section: Discussionmentioning
confidence: 99%
“…How might the overexpression of Cav-1 and caveolae contribute to the hyperproliferative phenotype of IPAH? Certain neoplasms [i.e., prostate cancer (39,40), bladder cancer (41), adenocarcinomas (42), esophageal squamous cell carcinomas (43), and both benign and malignant smooth muscle tumors (44)] have elevated Cav-1 expression. Timme et al have shown an interplay between Cav-1 and c-Myc-induced apoptosis: the Cav-1 gene can be down-regulated by c-myc, and maintaining high levels of Cav-1 suppresses c-myc-induced apoptosis (45).…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin 1 apparently plays a tumour suppressive function by virtue of its caveolin scaffolding domain (residues 82-101), which binds and inhibits several pro-oncogenic signalling molecules, such as SFK and MAP kinases. On the other hand, caveolin 1 has been defined as a prognostic marker for aggressive prostate, pancreatic and esophageal carcinoma, and an important mediator of hormone-dependent signal transduction [40][41][42]. In prostate cancer, the progression of malignancy has been shown to directly correlate with caveolin 1 expression levels [43], and caveolin ) transfected cells were subjected to Western blotting and probed with anti-caveolin antibody to detect endogenous and exogenously expressed caveolins and anti-GAPDH as a loading control.…”
Section: Discussionmentioning
confidence: 99%
“…105 In recent years, increasing evidence demonstrates that Cav1 is suppressed at the early stages of transformation and carcinogenesis, but upregulated and associated with cancer progression, metastasis and poor prognosis in later stages of various carcinomas. [106][107][108][109] Cav1 is not detectable in non-neoplastic livers, but HCC (26%) show increased expression. 110 In mouse HCC cell lines, cells with higher invasive ability have strong Cav1 expression.…”
Section: Caveolin-1 (Cav1)mentioning
confidence: 98%